Structural basis for oxygen degradation domain selectivity of the HIF prolyl hydroxylases - Rasheduzzaman Chowdhury (Nature Portfolio, 2016)
The response to hypoxia involves multiple genes regulated by the hypoxia inducible transcription factors (HIFs), whose stability is regulated by prolyl hydroxylation. Here the authors provide a molecular basis for the substrate selectivity of the HIF prolyl hydroxylases that can be altered in erythrocytosis and cancer.